Eco_Language: Edukasi Bank Sampah Berbasis Literasi Bahasa dan Teknologi pada Masyarakat Desa - Genisa, Risma Asriani Azis; Nihaya, Musdalifah; Sapan, Amika; Taufik, Muhammad Taufik; Yaumi, Muhammad Taufik Al Hakim; Absri, Absri (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
The coastal village of Boddia in Takalar Regency faces increasing waste pollution due to the community’s limited awareness of sustainable waste management. To address this issue, a community service initiative was implemented using the Eco-Language approach, which integrates language and technology literacy in educating residents through the establishment of a local waste bank. The program involved several stages: awareness-building sessions, training in waste-based product creation, digital marketing workshops, and the development of a community waste bank structure. Actively involving local residents, the program succeeded in enhancing environmental awareness, fostering practical skills, and generating marketable products. Collaboration between academics and local authorities played a crucial role in shaping a mindset shift toward circular economy practices. The outcomes suggest that this model holds strong potential for adaptation in other coastal areas facing similar environmental challenges.